Cardiac T2* Magnetic Resonance for Prediction of Cardiac Complications in Thalassemia Major - Paul Kirk; Sy Ha; John B. Porter; John M. Walker; Mark Tanner; Jitesh A. Patel; D. Wu; Janet L. Taylor; Mark A. Westwood; Lisa Anderson; Dudley J. Pennell (2009)
Background— The goal of this study was to determine the predictive value of cardiac T2* magnetic resonance for heart failure and arrhythmia in thalassemia major. Methods and Results— We analyzed cardiac and liver T2* magnetic resonance and serum ferritin in 652 thalassemia major patients from 21 UK centers with 1442 magnetic resonance scans. The relative risk for heart failure with cardiac T2* values <10 ms (compared with >10 ms) was 160 (95% confidence interval, 39 to 653). Heart failure occurred in 47% of patients within 1 year of a cardiac T2* <6 ms with a relative risk of 270 (95% confidence interval, 64 to 1129). The area under the receiver-operating characteristic curve for predicting heart failure was significantly greater for cardiac T2* (0.948) than for liver T2* (0.589; P <0.001) or serum ferritin (0.629; P <0.001). Cardiac T2* was <10 ms in 98% of scans in patients who developed heart failure. The relative risk for arrhythmia with cardiac T2* values <20 ms (compared with >20 ms) was 4.6 (95% confidence interval, 2.66 to 7.95). Arrhythmia occurred in 14% of patients within 1 year of a cardiac T2* of <6 ms. The area under the receiver-operating characteristic curve for predicting arrhythmia was significantly greater for cardiac T2* (0.747) than for liver T2* (0.514; P <0.001) or serum ferritin (0.518; P <0.001). The cardiac T2* was <20 ms in 83% of scans in patients who developed arrhythmia. Conclusions— Cardiac T2* magnetic resonance identifies patients at high risk of heart failure and arrhythmia from myocardial siderosis in thalassemia major and is superior to serum ferritin and liver iron. Using cardiac T2* for the early identification and treatment of patients at risk is a logical means of reducing the high burden of cardiac mortality in myocardial siderosis. Clinical Trial Registration— URL: http://www.clinicaltrials.gov. Unique identifier: NCT00520559.